ANALYSIS OF FACTORS INFLUENCING EMPLOYMENT OPPORTUNITIES IN WEST JAVA PROVINCE IN 2015-2020 - Akbar, Syuhada; Haerisma, Alivien Septian; Suharto, Toto (Politeknik Siber Cerdika Internasional, 2023)
The study aims to determine the impact of GRDP, PMDN, and FDI on job opportunities in West Java Province, either partially or simultaneously. This study used a quantitative research method which was conducted from January to June 2022. The data used came from the Central Statistics Agency (BPS) www.bps.go.id. The sampling technique used was purposive sampling. Processing flow the collected data is processed with SPSS version 20 and data testing is carried out, namely: Classical Assumption Test, Model Test, and Hypothesis Test. The results showed that GRDP had an effect on employment opportunities as evidenced by t count (17.485) > t-table (4.30265) and Sig count (0.003) < 0.05. PMDN affects the number of workers needed, t-count (133.218) > t-table (4.30265), and Sig count (0.000) < 0.05. Likewise, foreign investment has an effect on the required workforce with t-count (22.762) > t-table (4.30265) and Sig count (0.002) < 0.05. Gross Regional Domestic Product, Domestic Investment, and Foreign Investment have a simultaneous effect on employment opportunities, with F count (6247.864) > F table (19.00) and Sig count (0.000) < 0.05. So it can be stated that the GRDP, PMDN, and FDI variables simultaneously have a significant effect on the employment opportunity variable.